Application of Laser Scanning Technology in Geotechnical Works on Reconstruction of Draw Spans of the Palace Bridge in Saint Petersburg. (2017) - Kanashin, N.V.; Nikitchin, A.A.; Svintsov, E.S.
Abstract: The article describes the experience of applying technology of terrestrial laser scanning in geotechnical works while reconstructing the Palace Bridge in St. Petersburg. Engineering-geodetic work required the survey of draw span pier including its external elements and internal space with all equipment and machines, as well as the coordination of control points of the equipment attaching the truss about wing axis. The survey network included 2 stages. At the first stage we created its geodetic quadrangle framework the points of which were fixed by marks of temporary fixation – dowels driven into the draw span piers. For the survey extension was performed which required coordinates transmission (done by using polar resections) into each pier through their technological windows and passages. The survey network points inside the piers were fixed by scanner benchmarks. The survey was performed by terrestrial laser scanners. The main aim of the survey was 3D models of the structures. Modeling of the structure elements was done by integrating rigid-body geometric primitives into the point model being the result of the survey. Rigid-body geometric primitives were created as a pattern of one of Autodesk AutoCAD elements.